Alteração dimensional modelos de gesso tipo IV e V obtidos a partir de moldagem com polissulfeto, com duas espessuras - Miranda, Roberto Amaral (2006)
The aim of this study was to test the hypothesis of that the type of gypsum and the thickness of the impression material influence in the dimensional alteration of prosthetic models. Master-Model of mandibular arch was confectioned, using two extracted human teeth: an inferior first molar, first premolar and absence of inferior second premolar, completed with acrylic resin teeth. The human teeth had received prepares for metal-ceramic full crown, six reference points had been established in each tooth, resulting in seven measurements: mesiodistal, buccopalatine and occlusal-cervico for both, and teeth interpillars distance. The prepared teeth had been molded by the shell technique in acrylic resin with relief in 2 thicknesses: 0,8mm and 1,5mm, using regular polysulfide (n= 30). The moulds had been poured with three types of special plaster: natural type IV (Vel-mix), artificial (Tuff-Rock) and type V (Exadur). Three examiners measured the master-die and the samples in microscope of measurement with precision of 1mm. The data had been analyzed statistically by means of ANOVA and test of Tukey (a=0,05), demonstrating that it did not have difference statistics in function of the thickness of the impression material. However, significant variation in the distance interpillars was verified on the types of gypsum and between these and the master-die, when dental stone type IV demonstrated more steady behavior. The gypsums (Exadur, Vel-mix e Tuff-rock) showed vertical behavior dimensionality stable in 61% of the measures (horizontal and vertical) and significances statistics differences in 39%, representing expansion, 17% to Exadur, 14% to Vel-mix and 11% to Tuff-rock.